The Technician Commitment: its emergence, enactment and impact - Vere, Kelly (2022)
Technicians, who are often referred to as an ‘invisible workforce’, are key to research and teaching in universities. Given that a thriving technical workforce is critical to achieving the UK government’s post-Brexit ambitions for research and development, including making Britain a science superpower, the UK higher education sector needs improved knowledge and insight of its technical workforce. Historically, roles have been ill-defined and technicians’ contributions to the sector have not been well understood. Furthermore, an aging technical workforce means that large numbers of highly-skilled technicians are retiring every year with insufficient attention being paid to attracting a new generation of technicians to the sector. Consequently, recent reports have highlighted a shortage of technicians across all sectors in the UK.